A state-of-the-art review of direct observation tools for assessing competency in person-centred care. (September 2020) - Ekman, Nina; Taft, Charles; Moons, Philip; Mäkitalo, Åsa; Boström, Eva; Fors, Andreas
Highlights: 16 tools were identified. Conceptual underpinnings of the tools were generally unclear. Most reported inter-rater, internal consistency reliability and concurrent validity. Intra-rater reliability, content and construct validity were rarely reported. Predictive and discriminant validity were not assessed. Abstract: Background: Direct observation is a common assessment strategy in health education and training, in which trainees are observed and assessed while undertaking authentic patient care and clinical activities. A variety of direct observation tools have been developed for assessing competency in delivering person-centred care (PCC), yet to our knowledge no review of such tools exists. Objective: To review and evaluate direct observation tools developed to assess health professionals' competency in delivering PCC. Design: State-of-the-art review Data sources: Electronic literature searches were conducted in PubMed, ERIC, CINAHL, and Web of Science for English-language articles describing the development and testing of direct observation tools for assessing PCC published until March 2017. Review methods: Three authors independently assessed the records for eligibility. Duplicates were removed and articles were excluded that were irrelevant based on title and/or abstract. All remaining articles were read in full text. A data extraction form was developed to cover and extract information about the tools. The articles were examined for any conceptual or theoretical frameworks underlying tool development and coverage of recognized PCC dimensions was evaluated against a standard framework. The psychometric performance of the tools was obtained directly from the original articles. Result: 16 tools were identified: five assessed PCC holistically and 11 assessed PCC within specific skill domains. Conceptual/theoretical underpinnings of the tools were generally unclear. Coverage of PCC domains varied markedly between tools. Most tools reported assessments of inter-rater reliability, internal consistency reliability and concurrent validity; however, intra-rater reliability, content and construct validity were rarely reported. Predictive and discriminant validity were not assessed. Conclusion: Differences in scope, coverage and content of the tools likely reflect the complexity of PCC and lack of consensus in defining this concept. Although all may serve formative purposes, evidence supporting their use in summative evaluations is limited. Patients were not involved in the development of any tool, which seems intrinsically paradoxical given the aims of PCC. The tools may be useful for providing trainee feedback; however, rigorously tested and patient-derived tools are needed for high-stakes use.